Evolution of protectionism and FDI environment in the EU - Autere, Ria (My University, 2024)
The purpose of this bachelor’s thesis is to analyse the current two trends of the global economy, protectionism and FDIs, and how the trends have interacted in the context of EU. The EU provides a suitable context to the analysis since the union is deeply integrated both politically and economically. The subject is motivated by the recent trend of protectionism that has risen in the 2010s and has affected globally. The trend has been influencing in the background of, for example Brexit and the US-China trade war. It has influenced also on the EU legislation since it has taken a more protectionist shift. Another motivation to the thesis is the FDI’s more important role in the global economy. In the late 20th and the 21st the number of FDIs globally has increased drastically and they have a greater impact in the economy. Since the founding of the EU, the union has been hosting many inward FDIs and the FDI environment is traditionally described being open. The thesis aims to provide an analysis on how protectionism has shaped the FDI environment in the EU. This thesis will describe the EU as a FDI environment, go through the reasons behind protectionism in the EU and introduces the phenomenon of global protectionism. Lastly the thesis examines how the protectionism has shaped the FDI environment through legislation. As a politically integrated union, EU mostly acts through legislation to change its FDI environment. For this reason, the FDI environment in the EU region is unique and can be examine widely through different kinds of factors. The findings presented in this thesis are that the EU introduced a regulation about screening outside FDIs and that the regulation follows the trend of global protectionism. The regulation will decrease the inflow of FDIs into the EU and has made the EU’s traditionally open FDI environment more restrictive. However, the long-lasting effects of the regulation are still unclear since the regulation is relatively new.

Kanditutkielman tarkoituksena on analysoida maailmantalouden kahta nykyistä trendiä, protektionismia ja suoria ulkomaisia sijoituksia, sekä sitä, miten trendit ovat vaikuttaneet toisiinsa EU:n puitteissa. EU tarjoaa sopivan kontekstin analyysille, sillä unioni on syvästi integroitunut sekä poliittisesti että taloudellisesti. Aiheen taustalla on viimeaikainen protektionismin suuntaus, joka on noussut 2010-luvulla, ja vaikuttanut maailmanlaajuisesti. Suuntaus on vaikuttanut muun muassa Brexitin ja Yhdysvaltojen ja Kiinan välisellä kauppasodan taustalla. Nyt se on vaikuttanut myös EU-lainsäädäntöön, sillä se on ottanut protektionistisemman suunnan. Toinen motivaatio tutkielmalle on ulkomaisten suorien sijoitusten tärkeämpi rooli maailmantaloudessa. 1900-luvun lopulla ja 2000-luvulla suorien ulkomaisten sijoitusten määrä maailmanlaajuisesti on kasvanut rajusti, ja niillä on suurempi vaikutus talouteen. EU:n perustamisesta lähtien liitto on isännöinyt monia ulkomaisia suoria sijoituksia ja ympäristöä on perinteisesti kuvailtu avoimeksi. Tutkielman tavoitteena on tuottaa analyysi siitä, miten protektionismi on muokannut suorien sijoitusten ympäristöä EU:ssa. Tutkielmassa kuvataan EU:ta suorien sijoitusten ympäristönä, käydään läpi protektionismin taustalla olevat syyt EU:ssa ja esitellään maailmanlaajuisen protektionismin ilmiö. Lopuksi tutkielmassa tarkastellaan, miten protektionismi on muokannut sijoitusympäristöä lainsäädännön kautta. Poliittisesti integroituneena unionina EU toimii useimmiten lainsäädännön keinoin muuttaakseen suorien ulkomaisten sijoitusten toimintaympäristöä. Tästä syystä EU:n alueen suorien sijoitusten ympäristö on ainutlaatuinen ja sitä voidaan tarkastella laajasti erilaisten tekijöiden kautta. Tutkielmassa esitetyt havainnot ovat, että EU otti käyttöön asetuksen, joka koskee ulkopuolisten sijoitusten seulontaa, ja että asetus noudattaa trendiä maailmanlaajuisesta protektionismista. Asetus vähentää suorien sijoitusten virtaa EU:hun ja on tehnyt EU:n perinteisesti avoimesta toimintaympäristöstä rajoittavamman. Asetuksen pitkäaikaiset vaikutukset ovat kuitenkin vielä epäselviä, koska asetus on vielä suhteellisen uusi.
Keywords: protectionism, foreign direct investment, EU, screening mechanism